ANALISIS KADAR TIMBAL (Pb) PADA KERUPUK YANG DIPRODUKSI INDUSTRI RUMAHAN DI KECAMATAN GATAK KABUPATEN SUKOHARJO - Istiqomah, Ria; Jamilatun, Makhabbah; Yulianto, Susilo (Jurnal Medikes (Media Informasi Kesehatan), 2023)
Crackers are snacks that are very popular and are loved by Indonesian people. Making crackers by drying is carried out on the side of the road allowing lead contamination to occur. Lead is very dangerous if it enters the body in amounts exceeding permissible requirements. This research determined the content and levels of lead (Pb) in crackers produced by the Home Industry with samples of rice crackers, catfish crackers, cow skin crackers, and rengginang. Quantitative descriptive research method. Data collection by Purposive Sampling. The qualitative analysis method used a test tube with K2CrO4 reagent and quantitatively used ASA (Atomic Absorption Spectrophotometry) at a wavelength of 283.3 nm. The research was conducted at the Campus III Laboratory of the Surakarta Ministry of Health Polytechnic in January-April 2021. The results obtained showed levels of lead (Pb) in the "rice crackers", "lele crackers", "cow skin crackers", and "rengginang" samples, respectively of 3.43 mg/kg, -9.28 mg/kg, -9.38 mg/kg, and -9.73 mg/kg.